RENAISSANCE - Hale, J. R., (John Rigby), 1923-1999, author 390622; The Editors of Life-Time Books 9563 (Amsterdam, Netherlands : Time-Life Books, 1965)
A lavishly illustrated discussion of the events, ideas, artists and other major personalities of the Renaissance period in Italy.